General Solution and Stability of Additive-Quadratic Functional Equation in IRN-Space. (4th August 2021) - Tamilvanan, K.; Alessa, Nazek; Loganathan, K.; Balasubramanian, G.; Namgyel, Ngawang
Abstract : The investigation of the stabilities of various types of equations is an interesting and evolving research area in the field of mathematical analysis. Recently, there are many research papers published on this topic, especially additive, quadratic, cubic, and mixed type functional equations. We propose a new functional equation in this study which is quite different from the functional equations already dealt in the literature. The main feature of the equation dealt in this study is that it has three different solutions, namely, additive, quadratic, and mixed type functions. We also prove that the stability results hold good for this equation in intuitionistic random normed space (briefly, IRN-space).